Multicomponent Exercise Module: Guidelines for Improving Frailty, Hemodynamic Parameters, and Balance in Older Adults - Andreany Kusumowardani; R.A. Tuty Kuswardhani; I Made Muliarta; Luh Putu Ratna Sundari (Jurnal Kesehatan Vokasional, 2025)
Background: One in five Indonesian elderly was frail. Multicomponent exercise is one of the recommended strategies for frailty management in the elderly. However, it would be difficult for the elders to practice the exercise without proper exercise guidelines. In this study, a Multicomponent Exercise Program (MEP) module has been developed and implemented as exercise guidelines, but its effectiveness to improve physical performance of frail elderly has not been tested.Objective: The study aimed to determine the effectiveness of the MEP in the module to improve frailty, hemodynamic parameters, and balance in pre-frail and frail elderly.Methods: Quasi-experimental method was used in the study involving 17 participants (73.47 + 8.43 years). The MEP was conducted 3 times per week for 12 weeks, consisted of flexibility, balance, aerobic, and strength training. Categorical data were analyzed using McNemar's test while analysis of continuous data using paired t-test or Wilcoxon Signed Rank, α = 0.05.Results: The MEP decreased frailty scores, systolic, diastolic blood pressure, and mean arterial pressure (p < 0.000), and improved balance (p = 0.023) in the elderly. Furthermore, the program reduced the frailty status, as evidenced by 41.18% of frail participants becoming pre-frail and 5.88% participants shifting from pre-frail to robustness.Conclusion: The MEP in the module was effective to improve frailty, hemodynamic parameters, and balance in the elderly. However, this needs to be confirmed with larger samples and better research designs.